2022
DOI: 10.1021/acsearthspacechem.2c00088
|View full text |Cite
|
Sign up to set email alerts
|

Influence of H2SO4···H2O and (H2SO4)2 on the Hydrolysis of Formaldehyde: A Potential Source of Methanediol in the Troposphere

Abstract: The hydrolysis of formaldehyde [HCHO + H 2 O → H 2 C-(OH) 2 ] assisted by bimolecular acidic catalyst of X (X = H 2 SO 4 •••H 2 O and (H 2 SO 4 ) 2 ) under different concentrations of H 2 SO 4 and H 2 O was performed by quantum chemical calculations of CCSD(T)-F12a/cc-pVDZ-F12//M06-2X/6-311++G(3df,3pd) and the master equation method. The calculated results show that the hydrolysis reaction of HCHO catalyzed by X can occur through both HCHO•••H 2 O + X (one-step reaction) and H 2 O•••X + HCHO (stepwise reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 59 publications
3
6
0
Order By: Relevance
“…To understand this, the mechanism for the formation of methanediol (OHCH 2 OH) from the CH 2 O + H 2 O reaction is re-calculated. The barrier height for CH 2 O + H 2 O is ∼38 kcal mol −1 , which is in very good agreement with that from the recent study by Zhang et al 32 This barrier height is quite high for atmospheric reaction to form methanediol. Due to the high barrier heights, the reaction may lead to the formation of CH 2 O⋯H 2 O, as suggested by Zhang et al 32 The reported rate constants are in the range of (∼10 −10 cm 3 molecule −1 s −1 ), which are similar to the two body complex values.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…To understand this, the mechanism for the formation of methanediol (OHCH 2 OH) from the CH 2 O + H 2 O reaction is re-calculated. The barrier height for CH 2 O + H 2 O is ∼38 kcal mol −1 , which is in very good agreement with that from the recent study by Zhang et al 32 This barrier height is quite high for atmospheric reaction to form methanediol. Due to the high barrier heights, the reaction may lead to the formation of CH 2 O⋯H 2 O, as suggested by Zhang et al 32 The reported rate constants are in the range of (∼10 −10 cm 3 molecule −1 s −1 ), which are similar to the two body complex values.…”
Section: Resultssupporting
confidence: 91%
“…The barrier height for CH 2 O + H 2 O is ∼38 kcal mol −1 , which is in very good agreement with that from the recent study by Zhang et al 32 This barrier height is quite high for atmospheric reaction to form methanediol. Due to the high barrier heights, the reaction may lead to the formation of CH 2 O⋯H 2 O, as suggested by Zhang et al 32 The reported rate constants are in the range of (∼10 −10 cm 3 molecule −1 s −1 ), which are similar to the two body complex values. 32 Zhang et al have also reported the rate constants for the effect of H 2 O, H 2 SO 4 , HNO 3 , and CH 3 COOH on the CH 2 O + H 2 O reaction.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations